The U.S./Canada Convergence Thesis: Contrary Evidence from Nova Scotia - Gilson, Clive; Wagar, Terry (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1995)
The impact of P.C. 1003 on labour relations legislation in the various Canadian provinces can be both overestimated and underestimated. Many other elements and factors came together to produce a Canadian System of industrial relations in 1944. P.C. 1003 was both a result and a beginning.The American Wagner Act of 1935 and the pressure exerted in Canada by union leaders to obtain similar legislation in this country were two major factors. Some provincial legislations had established Systems of conciliation, through the federal and/or provincial Departments of Labour.A few previous laws prepared the way for P.C. 1003. The Quebec Trade Disputes Act of 1901 introduced mediation, conciliation and arbitration. Although the services were offered on a voluntary basis to interested parties, a certain number did use them, and that very fact contributed to the view that state intervention was normal. The federal legislation adopted in the first decade of the century had a similar impact, at least until its constitutionality was successfully attacked in 1925.After the Snider case, all Canadian provinces but one moved to "provincialize" the effect of the Industrial Disputes Investigation Act by adopting similar legislation. The 1937 Industrial Conciliation and Arbitration Act of British Columbia provoked much interest; and the 1943 Ontario Collective Bargaining Act was an important experimental prelude to P.C. 1003. The provisions of these acts were in most cases voluntary, but their application, whether mandatory or voluntary, helped to foster the belief that government intervention in labour disputes was normal, if not desirable. The first federal-provincial conference held on the subject in 1943 also helped to pave the way to the acceptance of the main elements of P.C. 1003.Because of the war situation and the urgency of keeping conflicts from becoming too disruptive, steps that could not have been taken in other circumstances became acceptable at that time. Thus the administrative machinery for certification and conciliation services was put in place. The "cost-plus" system of granting government contracts played a major role. Because P.C. 1003 was mandatory for all war industries, it applied to most of the unionized industries. The rest of the economy was covered by provincial laws, many of them simply extending P.C. 1003 provisions to labour disputes in provincial jurisdiction. These provisions were continued after the war under the National Emergency Transitional Powers Act. By 1948, all of the provinces had adopted a Labour Relations Act, under that name or another, containing the major features of P.C. 1003 and of the 1948 federal Industrial Relations and Disputes Investigation Act. In a sense, P.C. 1003 owed a lot to previous provincial laws, but subsequent legislation also owes a lot to P.C. 1003, especially with regard to the technical aspects of certification and the creation of labour boards.